Evaluation of the Process Steps of Pretreatment, Pellet Production and Combustion for an Energetic Utilization of Wheat Chaff - Weiß, Barbara D.; Glasner, Christoph (Frontiers in Environmental Science, 2018)
This paper investigates the potential energetic utilization of wheat chaff via combustion and necessary process steps such as pretreatment and pellet production as an example of stramineous biomass. Chaff is one out of three main fractions during harvesting and remains usually on the field. Vice versa, it is a potentially so far unexploited biomass resource, which could serve as renewable energy source. Simultaneously, exploiting wheat chaff could intensify the economic benefit of agricultural land use. The combustion application requires choosing an applicable firing system adjusted to the properties of chaff. The economic feasibility of the combustion application depends strongly on the technical effort, which depends on the fuel. Chaff consists mainly of husks and straw. Due to the low ash melting point and the high chlorine content of straw, it can be advantageous for the combustion to remove short straw from the chaff by sieving. To evaluate the combustion properties of presorted and original chaff the elemental composition, the net calorific value, the volatiles and ash content and the ash melting behavior were determined. The efficient logistic of chaff is decisive for its economic exploitation. This is in conflict with the low bulk density of chaff and the resulting high storage volume. Compressing chaff into pellets optimizes its handling. This vital step for an economic exploitation of chaff was therefore investigated by this study. Parameters such as water content of the feed, addition of binders and the geometry of the pressing die bores influence the pelletizing success significantly. Thus, these parameters were investigated in this study. The resulting pellets were characterized with standardized methods and compared to the requirements of EnPlus standards in terms of mechanical durability, amount of fines, bulk density and final moisture content. Finally, combustion experiments in a Large-scale Oven for Kinetics Investigation characterized the burnout behavior of the produced pellets. This was compared to pine wood pellets as conventional fuel. The performed investigations show that the pellet production and the subsequent combustion of wheat chaff pellets is a feasible approach for an energetic utilization.